2012
DOI: 10.1002/hep.24783
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum-tethered transcription factor cAMP responsive element-binding protein, hepatocyte specific, regulates hepatic lipogenesis, fatty acid oxidation, and lipolysis upon metabolic stress in mice

Abstract: CREBH is a liver-specific transcription factor that is localized in the endoplasmic reticulum (ER) membrane. Our previous work demonstrated that CREBH is activated by ER stress or inflammatory stimuli to induce an acute-phase hepatic inflammation. Here we demonstrate that CREBH is a key metabolic regulator of hepatic lipogenesis, fatty acid (FA) oxidation, and lipolysis under metabolic stress. Saturated FA, insulin signals, or an atherogenic high-fat diet can induce CREBH activation in the liver. Under the nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
222
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 167 publications
(238 citation statements)
references
References 28 publications
15
222
1
Order By: Relevance
“…Evidence implicates the PPAR␣-RXR␣ heterodimer in regulating lipid metabolism (19), whereas CREBH, independent of PPAR␣, induces a systemic inflammatory response upon ER stress (20). CREBH also modulates lipid metabolism in response to metabolic stress (21). However, the exact function of the PPAR␣-CREBH complex is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence implicates the PPAR␣-RXR␣ heterodimer in regulating lipid metabolism (19), whereas CREBH, independent of PPAR␣, induces a systemic inflammatory response upon ER stress (20). CREBH also modulates lipid metabolism in response to metabolic stress (21). However, the exact function of the PPAR␣-CREBH complex is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Creb3l3 (CREBH) is a transcription factor belonging to the cyclic AMP response element binding protein transcription factor (CREB/ATF) family 53) and has been reported to regulate the serum amyloid P-component (SAP) and C-reactive protein (CRP) gene expression in response to systemic inflammatory signaling in the liver 54) . In addition, CREB3l3 was shown to regulate gluconeogenesis via the modulation of the Pepck-c and G6Pase genes 55) as well as many genes involved in hepatic lipid metabolism 56) . Furthermore, others have suggested that Creb3l3 is a direct target of PPAR and that the induction of CREB3l3 is involved in nutritional regulation in the fasting state 57) .…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Genetically CREBH-deficient mice showed higher plasma triacylglycerol concentrations than wild-type mice, and this was due to inefficient triacylglycerol clearance catalysed by lipoprotein lipase [25]. More recently, Zhang et al showed that disruption of CREBH activity leads to massive accumulation of hepatic lipid metabolites and significant increases in plasma triacylglycerol levels in animals fed with an atherogenic high-fat diet (HFD) [26]. However, the role of CREBH in controlling insulin-and LXR-stimulated SREBP-1c production and hepatic lipogenesis by a pharmacological lipid-lowering agent remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%